Islet Cell Surface Antibodies in Graves’ Disease; As Organ Non-Specific Antibodies - Ahn, Il-Min (Korean J Intern Med, 1988)
To define ICA positiveness and its clinical correlation in AITD, ICSA were checked in Graves’ patients by indirect IF test using rat insulinoma (RINr) cells. Also Ig adherence to rat thyroid (FRTL(5)) and EB virus cloned human B lymphocytes that do not produce immunoglobulins were measured as the same method of ICSA with determination of organ specific antibodies in the sera. The incidence of ICSA in Graves’ disease was 23.1 % (9/39) and the degree of the positiveness measured as % binding was roughly correlated to those of Ig adherence to FRTL(5) and B cells. This ability to bind multiple organs of different species was not found to have any correlation with the titers of organ specific antibodies, but the incidence of organ specific antibody positiveness was much higher in the ICSA positive sera. Also there was a significant difference on the absorption pattern to FRTL(5) and RINr cells between the sera of ICSA positive IDDM and Graves’ patients, where absorption and % binding to FRTL(5), cell in ICSA positive diabetic sera were significantly lower than those to RINr cells in ICSA positive Graves’.